Outcome following emergency laparotomy in 33 UK donkeys: A retrospective multicentre study - Merridale-Punter, Mathilde S; Prutton, Jamie S W; Stefanovski, Darko; Worsman, Francesca C F; Payne, Richard J; Wylie, Claire E; Archer, Debra C; Menzies-Gow, Nicola J; Coles, Lydia; McGovern, Kate F; Parker, Russell A (Equine veterinary journal, 2023)
Emergency laparotomies in donkeys are infrequently performed and there is limited literature on the subject. To determine findings and associated outcomes of exploratory laparotomies in donkeys. Descriptive retrospective study. Donkeys undergoing emergency exploratory laparotomy for investigation and treatment of colic at seven UK referral hospitals between 2005-2017 were included. Data were retrieved from available hospital records. Descriptive statistics and inferential statistical analysis of outcomes of interest was performed in three steps. Thirty-three cases fulfilled the inclusion criteria. Clinical signs on presentation were available for 32 donkeys, of which 53.1% (17/32) presented for investigation of colic while in 46.9% (15/32) the presenting complaint was non-specific. Primary lesion location included small intestine (42.4%, 14/33), large colon (39.3%, 13/33), caecum (6.1%, 2/33), stomach (6.1%, 2/33) and 6.1% (2/33) had multiple abnormal findings without a clear primary lesion. Overall survival to discharge was 54.5% (18/33). Five donkeys (15.2%, 5/33) were euthanased at surgery and of those recovering from general anaesthesia a further 35.7% (10/28) were euthanased or died prior to discharge. Six donkeys (21.4%, 6/28) required a second laparotomy of which 4 (66.7%, 4/6) survived. Post-operative complications occurred in 82.1% (23/28) of cases and included hyperlipaemia (42.9%, 12/28), incisional complications (21.4%, 6/28), ileus (21.4%, 6/28) and persistent colic (17.9%, 5/28). When adjusted for other complications, donkeys with primary gastric lesions were less likely to have presented with severe colic compared with those with primary small intestinal lesions (OR: 0.07, 95% CI 0.01-0.95, p = 0.05). Only age was positively associated with death prior to discharge (OR: 1.18, 95% CI 1.03-1.36, p = 0.02). Small sample size and retrospective design. Donkeys with abdominal lesions may present with a range of signs often not including colic. Surgical findings were diverse and survival to discharge appears to be lower than in horses.